Modeling and design of PV grid integration for GA-PSO based on fluctuating power quality - Vanam Satyanarayana; Vairavasamy Jayasankar (Institute of Advanced Engineering and Science, 2023)
Grid integration of renewable energy systems with majority of which is variable dc and variable ac. For example, solar systems output variable dc, while wind systems output variable ac. Power electronics now plays a significant role in the DC and AC conversion required for the grid. Power electronics now allows dc-coupled systems to be controlled for both active and reactive power, making inductively controlled for improving power quality and synchronizing renewable energy systems. The presence of harmonics in electrical systems indicates that current and voltage are distorted and deviate from sinusoidal waves; odd and even harmonics are the result of a nonlinear load. Voltage and sag and swell are examples of power quality issues, as are filters whose primary purpose is to reduce harmonics, voltage, and current in alternating-current power systems to an acceptable level. The maximum power point tracking is based on maintaining temperature and irradiance variables. We use both proposition and Maximum power point tracking (MPPT) to maximize PV power with oscillation tracking. The genetic algorithm with partial swarm optimization (GA-PSO) algorithm based on various optimization control techniques. Control techniques are proposed for systems with various unbalanced voltages to maintain control operation during fault conditions.